Craniofacial anthropometry: measurement comparison between contact and non-contact method - Fazli, Mohd. Kamil; Setan, Halim; Majid, Zulkepli (2006)
Modelling and measurement of the human face have been increasing by importance for various purposes. One of the purposes is craniofacial anthropometry or human face measurement. This paper is focused on measurement comparison between contact and non-contact method for craniofacial anthropometry. Mannequin is the type of data used in this research. The mannequin are scanned using two laser scanner VIVID910 to create the 3D model. Then the measurement will be made on that 3D model based on landmarks of human face. All the measurements are compared with contact method (caliper and microscribe). The result from this comparison shows which method is more precise.